2020
DOI: 10.1155/2020/1817931
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinicopathological Significance of PD-L1 in Patients with Cholangiocarcinoma: A Meta-Analysis

Abstract: Background. In recent years, there is growing literature on the prognostic significance of programmed death-ligand 1 (PD-L1) in cholangiocarcinoma (CCA); however, data have been conflicting. Therefore, the objective of this study was to assess the correlation between PD-L1 and prognosis in CCA through meta-analysis. Methods. Published studies were retrieved from the Web of Science, PubMed, Embase, and Cochrane Library up to April 17, 2020. The relationships between PD-L1 expression and survival outcomes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Data regarding the predictive value of PD-1 and PD-L1 expression on patient outcome are discordant and conflicting. One recent meta-analysis of 11 studies with more than 1000 patients showed that the expression of PD-L1 by tumor cells does not correlate with a worse overall survival of the patients even after stratifying by type of CCA [89] , but another meta-analysis provided opposite results [90] . As for PD-1, recent work has shown that, in iCCA, the increase in CD68 + macrophages and CD8 + T lymphocytes expressing PD-1 correlates with a worse postoperative survival [91] .…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Data regarding the predictive value of PD-1 and PD-L1 expression on patient outcome are discordant and conflicting. One recent meta-analysis of 11 studies with more than 1000 patients showed that the expression of PD-L1 by tumor cells does not correlate with a worse overall survival of the patients even after stratifying by type of CCA [89] , but another meta-analysis provided opposite results [90] . As for PD-1, recent work has shown that, in iCCA, the increase in CD68 + macrophages and CD8 + T lymphocytes expressing PD-1 correlates with a worse postoperative survival [91] .…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…As such, high levels of tissue Krebs von den Lungen 6 (KL-6 mucin)[ 63 ], cadherin-17 (CDH17)[ 64 ], kallikrein-11[ 65 ], uPAR[ 59 ] and high levels of serum cytokine-induced apoptosis inhibitor 1 (CIAPIN1)[ 66 ], MUC5AC[ 55 ], OPN[ 50 ], S100A6[ 67 ] and uPAR[ 59 , 68 ] were found adverse prognostic factors for CCA patient’s survival. Subjected to meta-analysis, high levels of tissue PD-L1[ 17 ] and tissue protein S100P[ 69 ] were also proposed as potential prognostic markers of CCA. Out of a protein multimarker panel consisting of serum S100A9, MUC5AC, TGF-β1, Ang-2, and CA19-9, serum levels of TGF-β1 and Ang-2 provided predictive potential for both metastasis and TNM stage prognosis in CCA patients[ 62 ].…”
Section: Proteinsmentioning
confidence: 99%
“…Moreover, alteration in targetable pathways [ e.g., fibroblast growth factor receptor 2 gene (FGFR2) involved in MAP kinase signaling, isocitrate dehydrogenase 1 and 2 (IDH1, IDH2)] were also depicted in CCA patients[ 16 ] and currently, several clinical trials are actively recruiting patients. Nevertheless, several microRNAs (miRs) expressions in tissue or deregulated immune responses [expression levels of cytotoxic T-lymphocyte antigen 4 (CTLA-4), forkhead box P3 (FOXP3), and programmed death-ligand 1 (PD-L1)] might have predictive capabilities in CCA patients[ 17 , 18 ]. Many other diagnostic and prognostic tissue-derived biomarkers have already been previously described[ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immune system plays an important role in the pathogenesis of biliary tract tumors [28]. Several studies have shown that PD-L1 expression occurs in half of patients and correlates with a poor prognosis [29]. Immune checkpoint inhibitors have been studied in early clinical trials in patients with biliary tumors.…”
Section: Pd-1/pd-l1 Inhibitionmentioning
confidence: 99%